DGI-077 Use of Everolimus in Combination with Exemestane For the Treatment of Advanced Breast Cancer in a Tertiary Hospital. (12th March 2013) - Sanchez, M; ALCACERA, MA; Gimeno, M; Allende, MA; Arenere, M; Fernández, E
Abstract : Background: Everolimus has recently been approved by the European Medicines Agency (EMA) for the treatment of postmenopausal women with advanced breast cancer in combination with exemestane, after treatment failure with letrozole or anastrozole. The approval was based on the results of the BOLERO-2 study. Purpose: To compare the use of everolimus plus exemestane in breast cancer in our hospital with the Bolero-2 study. Materials and Methods: Retrospective study of all patients treated with everolimus in combination with exemestane from September 2011 to September 2012. Data source: clinical history and Pharmacy Department records. The following variables were analysed: age, disease stage, metastases and localization, previous treatment, adverse reactions, duration of treatment, discontinuation of treatment and reasons. Safety was evaluated by the appearance of adverse reactions. Results: 9 patients with stage IV breast cancer were included. The median age was 54 (range 76–45) years. All patients had bone metastases and 2 had also visceral involvement (pulmonary and hepatic). Previous treatment included: letrozole/anastrozole (7), tamoxifen (6), fulvestrant (5) and chemotherapy (8). 5 patients met the inclusion criteria of the BOLERO-2 study. The most frequent reason for discontinuation in the BOLERO-2 study was disease progression. In our study 7 patients discontinued, the reasons were: disease progression (3), death (2), and unknown (2).The median duration of treatment was 16 weeks (14.6 weeks in the BOLERO-2 study). 2 patients are still continuing with the treatment. The main side effect was stomatitis (55.6%) as in the BOLERO-2 study. Other side effects in our study were: epistaxis, rash, fatigue, infection and gastrointestinal reactions. Conclusions: 55.55% of patients met the inclusion criteria of the BOLERO-2 study and the median duration of treatment was similar. Stomatitis was the main adverse effect observed. No conflict of interest.